Effect of β-blocker on clinical outcomes in patients with traumatic brain injury: a retrospective propensity-matched study - Zhang, Yaxin; Liu, Tingting; Ji, Wenwen; Wang, Guangdong (Frontiers in Pharmacology, 2025)
BackgroundTraumatic brain injury (TBI) represents a significant public health challenge due to its complex management. β-blockers may offer neuroprotective benefits, but their impact on TBI outcomes remains unclear. This study aims to evaluate the effect of β-blocker use on clinical outcomes in TBI patients.MethodsThis retrospective cohort study included adult TBI patients, categorized into β-blocker and non-β-blocker groups. Propensity score matching (PSM) was utilized to balance baseline characteristics. Mortality was assessed through the application of multivariable Cox regression models and Kaplan–Meier survival curves. Subgroup analyses examined the consistency of the results.ResultsA total of 1,516 patients were included in the study, with 750 receiving β-blocker therapy and 766 not receiving it. After PSM, 473 pairs of patients were matched. The analysis indicated that β-blockers significantly reduce 28-day mortality (HR 0.43, 95% CI: 0.31–0.60, P < 0.001). However, patients receiving β-blocker had considerably longer hospital stays (7.89 days vs. 5.45 days, P < 0.001) and ICU stays (2.94 days vs. 2.33 days, P < 0.001).Conclusionβ-blocker therapy is associated with improved short-term outcomes in patients with TBI, particularly in those with mild (GCS 13–15) and severe (GCS 3–8) TBI. However, no significant benefit was observed in patients with moderate TBI (GCS 9–12). This therapy may also prolong hospital and ICU stays.